Optical Properties of Ldpe Films with different Additives Mixtures (2011)
In this article, different formulations of linear low density polyethylene (PEBD) mixed with 5 different types of additives were processed, the objective of which is to analyze the effect of the additives on the optical properties of PEBD films for crop protection directed primarily for constructions of greenhouses suitable for performance in tropical environments. The results of the ultra violet and visible region transmission show that the light transmission of the reference films is greater in the visible area than in films made with additive mixtures, due to the diffusive effect of some elements and the synergistic action of the additives decreasing the transmission of light in the ultra violet and visible area.